1995
DOI: 10.1523/jneurosci.15-09-06213.1995
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor in Alzheimer's disease: increased levels throughout the brain coupled with declines in nucleus basalis

Abstract: The current study analyzed NGF protein levels in the brains of patients with Alzheimer's disease (AD) as compared with aged neurologically normal individuals. An established two-site ELISA was used to measure NGF-like immunoreactivity in the hippocampus, superior temporal gyrus, superior frontal gyrus, inferior parietal lobule, frontal and occipital cortical poles, cerebellum, amygdala, putamen, and nucleus basalis of Meynert (nbM). ChAT activity was assayed in adjacent tissue samples. NGF levels were also eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
1
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(138 citation statements)
references
References 53 publications
6
128
1
3
Order By: Relevance
“…Our finding of increased NGF in the hippocampus of Ts65Dn vs. 2N mice at 6 months of age suggested that decreased availability of NGF at BFCN terminals was not a factor. Hippocampal NGF mRNA or protein levels have similarly been reported as unchanged or even increased in AD patients (25,26). NGF levels are reduced in the basal forebrain as a whole (26) and specifically within BFCNs (26,27) in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding of increased NGF in the hippocampus of Ts65Dn vs. 2N mice at 6 months of age suggested that decreased availability of NGF at BFCN terminals was not a factor. Hippocampal NGF mRNA or protein levels have similarly been reported as unchanged or even increased in AD patients (25,26). NGF levels are reduced in the basal forebrain as a whole (26) and specifically within BFCNs (26,27) in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Hippocampal NGF mRNA or protein levels have similarly been reported as unchanged or even increased in AD patients (25,26). NGF levels are reduced in the basal forebrain as a whole (26) and specifically within BFCNs (26,27) in AD. Of note, we detected a trend toward decreased NGF levels in the septum of Ts65Dn mice.…”
Section: Discussionmentioning
confidence: 99%
“…choline acetyltransferase (ChAT) and acetylcholinesterase (AChE) with a decrease of cholinergic transmission (Svendsen et al, 1991;Venero et al, 1994). In contrast, the levels of proNGF, a precursor of NGF, which is the predominant form in human and rodent brain, are doubled in frontal and occipital cortex and in hippocampus in late-stage AD (Crutcher et al, 1993;Scott et al, 1995;Narisawa-Saito et al, 1996;Hellweg et al, 1998;Hock et al, 2000;Fahnestock et al, 2001;Peng et al, 2004) and appear to be 40%-50% increased in individuals with mild cognitive impairment (MCI) (Peng et al, 2004), suggesting that an unbalance in NGF processing may contribute, and in some instances cause, the onset of AD neurodegeneration. In this regard, an unbalance of the cascade of protease complex (plasminogen/plasmin; tPA,Neuroserpin, MMP-9) leading to a deficit of proNGF/NGF has been recently reported in human AD brains (Bruno et al, 2006;Cuello and Bruno, 2007).…”
Section: Ngf and Its Receptors In Admentioning
confidence: 99%
“…In addition, NGF levels are increased in cerebral cortex and decreased in nucleus basalis in Alzheimer's disease (Scott et al, 1995), suggesting that this disease could be associated with impaired TrkA-dependent retrograde transport of NGF. It is possible that the decreases in TrkA expression and retrograde transport are simply consequences of other processes that are responsible for the etiology of Alzheimer's disease.…”
Section: Alzheimer's Disease and Retrograde Transportmentioning
confidence: 99%